Role of dehydration temperature on flavonoids composition and free-form volatile profile of raisins during the drying process. (16th April 2022) - Chen, Keqin; Hu, Yujie; Chen, Li; Zhang, Junxia; Qiao, Haorong; Li, Wanping; Zhang, Kekun; Fang, Yulin
Graphical abstract: Highlights: Drying temperature modulated endogenous metabolite composition in raisins. Different drying temperatures promoted specific flavonoids accumulation. The volatile profiles of raisins varied with the drying temperature. Abstract: This study investigated the metabolic differences of 'Zicui' raisins produced at different drying temperatures (30 °C, 40 °C and 50 °C). Glucose, fructose, malic acid, shikimic acid and succinic acid contents were the highest in raisins dried at 50 °C. Compared with others, the drying temperature of 40 °C was more conducive to the accumulation of chalcones, dihydroflavones, dihydroflavonols, flavanols, flavonoid carbonosides, proanthocyanidins, and other phenols, while the drying temperature of 30 °C was more conducive to the accumulation of anthocyanins, flavonoid, and flavonols. Most volatile ketones and acids accumulated more in raisins produced at 30 °C, of which the content of 2, 6-dimethyl-4-heptanone with sweet odour reached 70.34 μg/L, significantly higher than that in other raisins. Overall, the appropriate drying temperature should be selected according to the demand for specific nutritional or aromatic metabolites during raisins production.